“Do You Trust Him?” Children’s Trust Beliefs and Developmental Trajectories of Aggressive Behavior in an Ethnically Diverse Sample - Malti, Tina (Springer US, 2012)
This study investigated the role of trust beliefs (i.e., trustworthiness, trustfulness) on aggression trajectories in a four-wave longitudinal study using an ethnically diverse sample of 8- to 11-year-old children (N = 1,028), as well as the risk profiles of low trust beliefs and low socioeconomic status on aggression trajectories. At Time 1 to Time 4, teachers provided ratings of overt aggressive behavior. At Time 1, children’s trust beliefs were assessed by a sociometric peer nomination instrument and derived using social relations analysis. Latent growth curve analysis revealed five trajectories of aggressive behavior: high-stable, medium-stable, low-stable, increasing, and decreasing. As hypothesized, children in the high-stable trajectory were perceived as less trustworthy than children in the low-stable, medium-stable, and increasing trajectories. Children in the high-stable trajectory were less trustful than children in the low-stable trajectory and had a significantly higher risk profile (i.e., low trust beliefs and low SES) compared to children in the low-stable trajectory. Our findings indicate that the developmental course of aggression during middle childhood is predicted by children’s trustworthiness and trustfulness. A risk profile of low trust and low socioeconomic status contributes to high-stable aggression trajectories.